Trauma and Posttraumatic Stress Disorder as Important Risk Factors for Gestational Metabolic Dysfunction - Rocha, Mariana; Daniels, Keziah; Chandrasekaran, Suchitra; Michopoulos, Vasiliki (American Journal of Perinatology, 2024)
Gestational metabolic diseases adversely impact the health of pregnant persons and their offspring. Pregnant persons of color are impacted disproportionately by gestational metabolic disease, highlighting the need to identify additional risk factors contributing to racial-ethnic pregnancy-related health disparities. Trauma exposure and posttraumatic stress disorder (PTSD) are associated with increased risk for cardiometabolic disorders in nonpregnant persons, making them important factors to consider when identifying contributors to gestational metabolic morbidity and mortality health disparities. Here, we review current literature investigating trauma exposure and posttraumatic stress disorder as psychosocial risk factors for gestational metabolic disorders, inclusive of gestational diabetes, low birth weight and fetal growth restriction, gestational hypertension, and preeclampsia. We also discuss the physiological mechanisms by which trauma and PTSD may contribute to gestational metabolic disorders. Ultimately, understanding the biological underpinnings of how trauma and PTSD, which disproportionately impact people of color, influence risk for gestational metabolic dysfunction is critical to developing therapeutic interventions that reduce complications arising from gestational metabolic disease.Key Points
Keywords: trauma; PTSD; stress; metabolic disorders during pregnancy; gestational diabetes mellitus; hypertensive disorders of pregnancy; fetal growth restriction